Improving BER using RD Code for spectral amplitude coding optical CDMA network - Fadhil, H.A; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org